Impact of Wire Feed Speed and Heat Input on Microstructure and Mechanical Properties in the Coarse-Grain Heat Affected Zone of Low Carbon Steel - Raj, Kershwin; Saifulnizan Jamian (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This thesis investigates the behavior of the Coarse-Grained Heat-Affected Zone (CGHAZ) in low carbon steel (AISI 1018) welded using Gas Metal Arc Welding (GMAW) under automotive manufacturing conditions. The study focuses on two primary welding variables: heat input and wire feed speed, assessing their impact on the microstructure and mechanical properties of the CGHAZ. Comprehensive testing includes Vickers hardness for wear resistance, Charpy V-notch for toughness, and 3-point bending for flexural strength. Statistical and qualitative analyses identify correlations between welding parameters and CGHAZ characteristics. The research aims to optimize welding settings to improve the quality and performance of welded components in automotive applications.